The influence of athletes irrational beliefs and perfectionism on competitive anxiety - Tóth, R.; Turner, M. J.; Kökény, T.; Tóth, L. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
Introduction In this research, we investigated the influence of irrational beliefs (demandingness, awfulizing, low frustration tolerance, depreciation) and perfectionism (adaptive and maladaptive) on competitive anxiety (cognitive and somatic) in Hungarian amateur and professional athletes. Previous studies have shown that irrational beliefs are able to predict the emergence of competitive anxiety. Furthermore, greater irrational beliefs have been linked to greater perfectionism as well. The association between irrational beliefs and perfectionism and their combined effect upon anxiety has not been investigated in sport contexts. Hence, we hypothesized that the influence of irrational beliefs on competitive anxiety is mediated by perfectionism. Methods Competitive anxiety (CSAI-2), irrational beliefs (iPBI) and perfectionism (SAPS) were measured by questionnaires in 219 Hungarian athletes. We ran the descriptive statistics and Pearson intercorrelations of all the normal distributed variables using IBM SPSS program. Hayes model 6 was used to test the direct and indirect effects of irrational beliefs and perfectionism on competitive anxiety. Results In serial atemporal multiple mediation analysis, we found that both adaptive and maladaptive perfectionism have a significant partial mediator role in the relationship between irrational beliefs and competitive anxiety. Both the total irrational beliefs score and the four subscale scores have direct and indirect effects on cognitive competitive anxiety where adaptive and maladaptive perfectionism playing a mediator role. Depreciation beliefs had a direct, demandingness and awfulizing had an indirect effect on somatic competitive anxiety when both forms of perfectionism were mediators. Discussion These findings support our hypothesis that irrational beliefs and perfectionism are influence on the emergence of competitive anxiety in Hungarian athletes. Overall, athletes who set dogmatic standards for themselves and are not able to handle frustration, tend to awfulizing and disparagement themselves face greater competitive anxiety. The following process is influenced by perfectionist traits such as overly high expectations and a disproportionate focus on mistakes. The obtained findings have important practical application for sport psychologist because based on our results rational emotive behavior therapy (REBT) may be an effective intervention to reduce perfectionism and competitive anxiety in athletes, the specific effectiveness of this intervention with athletes requires further longitudinal research.